The encyclopedia of human resource management (Pfeiffer, 2012)
The three volumes in The Encyclopedia of Human Resource Management offer a comprehensive review of the essential issues and most important information available on the topic. Each volume in the encyclopedia contains contributions from some of the most celebrated names in the field of human resource management (HRM) and addresses the myriad challenges faced by today's human resource professionals.